Enhanced hydrophilicity for TiO2 nanotube array by simultaneous nitrogen plasma and thermal annealing treatments - Chanawee Sattha; Aparporn Sakulkalavek; Rachsak Sakdanuphab (My University, 2018)
In this work, highly ordered TiO2 nanotube (TNTs) array was fabricated by electrochemical anodization technique on titanium sheet. Simultaneous N2 plasma and thermal annealing process were employed on TNTs using different N2 gas flow rates at 500 °C. As-anodized and N2 plasma TNTs were characterized for their microstructure, surface elemental composition, and wettability by scanning electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy (XPS), and contact angle measurement, respectively. It was found that N2 plasma and thermal annealing treatments affect to the change of crystal structure, surface chemistry and wettability of TNTs. The N2 plasma TNTs exhibits anatase phase with the orientations of (101) and (200). XPS spectra show that the nitrogen atom from plasma was introduced into the surface of TNTs and depends on the N2 gas flow rates. From contact angle measurement, it can be observed the improvement of wettability (hydrophilicity) of the TNTs due to the N-doped TiO2 nanotube after N2 plasma and thermal annealing treatments.
Keywords: Anodizing; Ion-surface interactions and analysis